An assesment of the performance of reform in Nigeria and Malaysian national health scheme programme - Ibrahim, Yahya Saleh; Jamal Khan, Mohamad Khan (Center for Promoting Ideas (CPI), USA, 2011)
The study assessed the performance of health care and safety services reform in Nigeria and Malaysian National Health Scheme.Survey method of research was adopted using questionnaire as the major tool of data collection.The data collected through the questionnaire method were subjected to Difference-in-Difference econometric statistical model analyses.The aim was to arrive at a conclusion on the comparative analysis of health care reform in the two countries (Nigeria and Malaysia), and as well between two periods (before and after reform). The findings revealed an impressive result supporting health care reform in the two countries.The comparative analysis also revealed a result showing the superiority of Malaysian healthcare reform over that of Nigeria.The result of performance testing of the reform before and after shows that the reform impacted positively on healthcare and safety services delivery to the employees in both Nigeria and Malaysia.The study concludes that, reform is one of the varitable tools to use in improving health care and safety services performance in Nigeria and Malaysia.